Supply-Chain Perturbations and Multi-Platform Robustness in Honey Authentication: Implications for Emerging New Zealand Monofloral Honeys - Wu, Yaoyang (Exploring Science Academic Conference Series, 2026)
New Zealand monofloral honeys beyond mānuka, including rewarewa and kāmahi, require authentication systems that remain reliable under realistic supply -chain conditions rather than under idealized laboratory settings alone. This review evaluates how three c ategories of supply-chain perturbation affect authentication- relevant chemical markers. Thermal processing alters volatile and phenolic domains in a marker -specific manner while leaving trace elements comparatively stable. Filtration and ultrafiltration se lectively remove pollen and certain non-volatile markers, although the evidence base for ultrafiltration-specific effects remains limited. Syrup adulteration distorts elemental ratios and can be detected through targeted small -molecule markers, but discriminatory power may weaken during post -adulteration storage. A comparative assessment of four analytical platform categories (GC-MS, LC-MS/MS, ICP-MS, and rapid spectroscopic methods) shows that each carries a distinct vulnerability profile and that no single platform provides uniform robustness across all perturbation types. On this basis, this review proposes a Sentinel Stress -Testing Framework for future authentication claims, comprising perturbation -aware challenge tiers, mandatory external validation on independent sample sets, and multi -block data fusion to exploit cross -platform redundancy. This framework provides a transferable basis for future commercial.